LECTURER TALK IN THE EMI CLASSROOM: A SPEECH ACT ANALYSIS - Sri Lestari; Ira Mutiaraningrum (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2023)
Research in the area of utilizing English as a medium of instruction hasoverlooked the investigation of communication issues among lecturersteaching their disciplines in English. This study seeks to determine the mostcommon speech act employed by lecturers utilizing English as a medium ofinstruction, the rationale behind the selection, and its implication onpedagogy and education. Employing a case study, we recruited fourinstructors from Biology and Primary Education who teach content-basedsubjects in English. With Searle's framework of speech acts, the studyrevealed that assertive speech acts were used 42.85%, directive 25.8%,expressive 21.65%, and commissive 9.6%. The findings indicate that mostlecturers used assertive speech acts to clarify content and engage studentsin achieving learning objectives. This study expected to give contributionas reflection tool on how speech acts should be performed in teachingprocess to promote successful English utilization by instructors teachingnon-English subjects.